1995
DOI: 10.1111/j.1365-2109.1995.tb00908.x
|View full text |Cite
|
Sign up to set email alerts
|

Artificial reproduction and fingerling production of the African catfish, Clarias gariepinus (Burchell 1822), in protected and unprotected ponds

Abstract: In order to obtain an appropriate and reliable method for the mass production of Clarias gariepinus (Burcheli) fingeriings. experiments on artificial reproduction and pond rearing were carried out in the Republic of Congo in 1987-1991. Reproduction could be Induced throughout the year using common carp pituitaries (3 mg kg'' female). The average relative fecundity of females varied between 1.3% ± 0.3 (SEM) and 14.37o ±1.3 (SEM). The average hatching percentage of the eggsvariedbetween28.4%±4.5(SEM)and59.1%± … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
47
1

Year Published

2002
2002
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(63 citation statements)
references
References 8 publications
4
47
1
Order By: Relevance
“…Stripping percentage also varied significantly (p<0.05) among the fish collected from different rivers and was highest in magur from Godavari [14.57±1.026 (P); 11.82±0.184 (O)], followed by Krishna [9.74±0.286 (P); 9.90±1.149 (O)] and Narmada [10.04±0.498 (P); 9.17±0.457 (O)]. Similar values were observed in closely related species Clarias gariepinus (De Graaf et al, 1995;Shinkafi and Ilesanmi, 2014). Since stripping process was involved in the breeding programme, PGSI is employed as an index in the present study according to Oyelese (2006) instead of GSI.…”
Section: Resultssupporting
confidence: 65%
“…Stripping percentage also varied significantly (p<0.05) among the fish collected from different rivers and was highest in magur from Godavari [14.57±1.026 (P); 11.82±0.184 (O)], followed by Krishna [9.74±0.286 (P); 9.90±1.149 (O)] and Narmada [10.04±0.498 (P); 9.17±0.457 (O)]. Similar values were observed in closely related species Clarias gariepinus (De Graaf et al, 1995;Shinkafi and Ilesanmi, 2014). Since stripping process was involved in the breeding programme, PGSI is employed as an index in the present study according to Oyelese (2006) instead of GSI.…”
Section: Resultssupporting
confidence: 65%
“…The non-significant differences may be attributed to the fact that the ovarian weight is usually a negligible fraction of the somatic (body) weight. de Graaf et al (1995) reported similar finding for Clarias gariepinus breed, using artificial propagation techniques. Delince et al (1987) reported that spent ovary of C. gariepinus represented about 10-20% of its initial weight.…”
Section: Discussionsupporting
confidence: 66%
“…gariepinus and H. bidorsalis show a seasonal gonadal maturation which is usually associated with the rainy season. The maturation processes of both species are influenced by annual changes in water temperature and photoperiodicity and the final triggering of spawning is caused by a rise in water level due to rainfall (de Graaf et al, 1995). Artificial reproduction in catfish species especially C. gariepinus and H. bidorsalis have been studied by several authors (Haniffa and Sridhar, 2002;Nwokoye et al, 2007;Akinwande et al, 2009;Ataguba et al, 2009;Owodeinde and Ndimele, 2011).…”
Section: Introductionmentioning
confidence: 99%